AB0595 Changes in serum creatinine in patients with active rheumatoid arthritis treated with TOFACITINIB (CP-690, 550). (23rd January 2014) - Isaacs, J.; Nduaka, C.; Zuckerman, A.; Krishnaswami, S.; Riese, R.; Lan, S.; Hutmacher, M.; Boy, M.; Bradley, J.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor that is being investigated as a targeted immunomodulator and disease-modifying therapy for rheumatoid arthritis (RA). Small increases in mean serum creatinine (SCr) have been observed with tofacitinib treatment in the clinical development programme. Objectives: To summarise changes in SCr and associated adverse events (AEs), to characterise dose-response relationships and to explore demographic and disease covariates of SCr. Methods: SCr values and associated AE data were pooled from five Phase 3 (P3) and two ongoing long-term extension (LTE) studies. Dose-response relationships and covariate analyses were performed on five Phase 2 (P2) studies comprising a 1-30 mg twice daily (BID) tofacitinib dose range using non-linear mixed effects models. Results: In pooled P3 studies, increases in SCr occurred predominantly within the first three months of tofacitinib treatment, resulting in mean SCr differences from placebo of 0.02 and 0.04 mg/dL for the 5 and 10 mg BID patients, respectively, at Month 3 (p<0.05). Patients with confirmed increases in SCr of ≥33% over baseline generally displayed stable or reduced levels over the remainder of the P3 study. Analysis of P2 tofacitinib data suggested a dose-response in mean SCr. Increases reached steady state levels in a typical patient by approximately six weeks and reversed in most patients two to six weeks after stopping tofacitinib treatment. Multivariate analysis showed an effect of age, gender, body weight, angiotensin-converting enzyme inhibitor use on baseline SCr only (p<0.05), while baseline C-reactive protein (bCRP) and Asian race predicted both baseline SCr and increases with tofacitinib treatment (p<0.05). Patients with higher bCRP had lower SCr at baseline and showed a larger absolute and fractional dose-dependent increase in SCr upon treatment with tofacitinib compared with those with lower bCRP. Of 3030 tofacitinib-treated patients participating in P3 studies, 0.3-0.7% across treatment groups experienced adverse events (AEs) that could be categorised as acute renal failure (ARF) according to MedDRA (Medical Dictionary for Regulatory Activities) Query. These MedDRA-defined AEs included laboratory abnormalities reported as "blood creatinine increased". AEs of ARF were predominantly seen in the setting of concurrent serious illness such as severe dehydration or sepsis in the P3 and LTE studies. Seventeen patients (0.56%) met SCr-based protocol criteria for discontinuation (two consecutive increases >50% from the mean of screening and baseline). Resolution generally occurred upon temporary or permanent discontinuation of tofacitinib. Conclusions: Tofacitinib treatment was associated with small mean increases in SCr, which were generally reversible. Changes in SCr appeared to be influenced by bCRP and race among patients with RA. The mechanism behind the changes in SCr is undergoing further investigation. MedDRA-defined ARF occurred infrequently with tofacitinib treatment in the P3 and LTE studies, was observed in the setting of concurrent illnesses associated with ARF in the general population and generally reversed on discontinuation of treatment. Disclosure of Interest: J. Isaacs Consultant for: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Zuckerman Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Riese Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Lan Employee of: Pfizer Inc, M. Hutmacher Consultant for: Pfizer Inc, M. Boy Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc